DEVELOPING ENGLISH SPEAKING SKILLS THROUGH ARTIFICIAL INTELLIGENCE - Zarifakhan Alijanova Sultonovna, (TADQIQOTLAR, 2026)
Abstract: The rapid advancement of artificial intelligence (AI) is revolutionizing various sectors, and education is no exception. Among the most promising areas where AI  is  making  a  significant  impact  is  language  learning,  especially  in  developing English  speaking  skills.  This  approach  promises  efficiency,  personalization,  and accessibility that traditional teaching methods often lack. Learning to speak English fluently is regarded as an essential skill in today’s globalized world. However, learners face numerous challenges such as a lack of access to proficient native speakers, limited practice opportunities, traditional teaching methods focusing more on grammar and writing and less on speaking, fear of making mistakes, and low confidence levels. In this  context,  AI  is  emerging  as  a  powerful  facilitator  to  tackle  these  obstacles effectively.